INVESTIGATION OF NEW INSTRUMENTATION AND TECHNIQUES FOR RAPID EVALUATION OF LOAD BEARING CAPACITY OF TEMPORARY ROADS, RUNWAYS AND COMPACTED AREAS (SNOW AND SOIL). - Terry,Cyrl W. (1966)
The purpose of this study was to develop instrumentation that would allow rapid evaluation of trafficability and load bearing capacity of roadways, airstrips and certain areas. The basic approach was through use of a recording probe or penetrometer, a device that records resistance to penetration vs. depth. Two models were tested: one was manually operated and the other was power operated by a hydraulic power unit and cylinder. (Author)